Konsep Pengembangan Evaluasi Berbasis Proyek dalam Pembelajaran Pendidikan Agama Islam - Juhaeni, Juhaeni; Adillah, Nur; Wafda, Wafda; Sir, Nadia Ulfah (Journal of Instructional and Development Researches, 2024)
This research aims to determine the concept of developing project-based evaluation in PAI learning. This research adopts a qualitative approach, which is an examination or investigation method that uses logical reasoning and analysis. Researchers use information data from various theories obtained through library research. The type of research applied is librarianship, which is based on documents such as books, scientific books, articles, magazines, and so on which can be accessed in libraries. Based on the results of literature research, it can be concluded that in integrating the concept of project-based evaluation development in Islamic Religious Education (PAI) learning, it can be concluded that this approach brings significant benefits to the learning process. Project-based evaluation not only measures students' understanding of Islamic teachings, but also involves them in practical activities that enable the application of these concepts in everyday life. By implementing projects that are relevant to the context of students' lives, this kind of evaluation not only assesses cognitive, but also aspects of religious practice, ethics and morality. Thus, the concept of developing project-based evaluation provides a holistic approach in assessing the understanding and application of Islamic religious values in students' real lives, which in turn can improve the quality of PAI learning and form a generation that has a strong commitment to Islamic religious teachings